Compras compartilhadas como ferramenta para a otimização dos processos de aquisições de materiais no âmbito da UTFPR - Brito, Juliano Camargo de (2021)
The provision of public services to society requires numerous purchases, which, as a rule, are carried out through competitive bidding. Within the scope of the Federal Executive Power, these processes occur independently. However, this scenario tends to change in the coming years, as the public procurement area has been going through an innovation process, both for the improvement of legislation, and for the implementation of new tools to government agencies, suppliers, and society in general. Among these changes, what stands out is the requirement to prepare the Annual Plan for the Procurement of goods, services, works, and technology solutions for information and communications, applicable to the Brazilian Federal Direct, Autonomous, and Foundational Public Administration. This plan, which aims to assist the manager in the planning and decision-making processes, has as one of its objectives the expansion of shared purchases between institutions and the feasibility of new opportunities for scale gains. In this context, there is an opportunity to carry out the research on screen, which has as main objective the development of a proposal that describes the necessary steps for the expansion of shared purchases within the scope of the Federal Technological University of Paraná – UTFPR. For the development of this study, the mixed research approach was used, in a field study carried out through bibliographic and documentary sources. For data collection, bids were carried out by the fourteen Administrative Units of General Services that are components of the UTFPR system (Rectory and thirteen Campus) during 2019, in the trading session, in electronic form, and whose object was the purchase of consumables and permanent materials. Through this procedure, a total of 207 processes were reached, which were organized and analyzed by the researcher through specific indicators contained in topic 3.4 of this work, as well as by experience accumulated over the years with the performance as Bidding Agent of Campo Mourão campus. The results obtained indicated the existence of, at least, three distortions that hinder the realization of shared purchases: decentralization of purchase planning; inexistence of a unified timetable, and repetition of similar processes between AUGSs. The final step consisted of developing a proposal with the description of the necessary steps for the expansion of shared purchases within the scope of UTFPR, being characterized as an incremental process innovation.